2020
DOI: 10.1021/acssuschemeng.0c03463
|View full text |Cite
|
Sign up to set email alerts
|

High-Strength Polylactic Acid (PLA) Biocomposites Reinforced by Epoxy-Modified Pine Fibers

Abstract: The stiffness and tensile strength of biopolymers (e.g., polylactic acid (PLA)) are less than desirable for load-bearing applications in their neat form. The use of natural fibers as reinforcements for composites (for large-scale three-dimensional (3D) printing) has expanded rapidly, attributable to their low weight, low cost, high stiffness, and renewable nature. Silane and acid/alkali are typically used to modify the surface of natural fibers to improve the fiber/polymer interfacial adhesion. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 39 publications
2
59
0
Order By: Relevance
“…They found the tensile strengths and Young's moduli of the epoxy-modified pine/PLA (0.5-10 wt%) composites increased by up to 20% and 82% respectively, as compared to those of neat PLA, which is attributed to epoxy partially immersing into the inner structures of pine fibers and thus improved the interfacial adhesion. 31 Sui et al prepared ternary PLA-based composites by a reactive and high-shear extrusion, in order to control well the phase morphologies and improve the properties. It is reported that the suitable dispersed phase size and appropriate interfacial adhesion led to an obvious enhancement of impact toughness, primarily benefited from the combined effect of reactive and high-shear extrusion.…”
Section: Introductionmentioning
confidence: 99%
“…They found the tensile strengths and Young's moduli of the epoxy-modified pine/PLA (0.5-10 wt%) composites increased by up to 20% and 82% respectively, as compared to those of neat PLA, which is attributed to epoxy partially immersing into the inner structures of pine fibers and thus improved the interfacial adhesion. 31 Sui et al prepared ternary PLA-based composites by a reactive and high-shear extrusion, in order to control well the phase morphologies and improve the properties. It is reported that the suitable dispersed phase size and appropriate interfacial adhesion led to an obvious enhancement of impact toughness, primarily benefited from the combined effect of reactive and high-shear extrusion.…”
Section: Introductionmentioning
confidence: 99%
“…Processes of PLA melt blending and molding require high operating temperatures above the polymer melting point (up to 200°C) and/or high pressures 16,19,22,24,39,56–68 . After being melted, PLA is shaped into the desired form by molding (with or without a mechanical press) and cooled down to stabilize its dimensions 23 …”
Section: Methods For Pla Processingmentioning
confidence: 99%
“…Blending of PLA with other polymers has been suggested for creation of materials with tailored mechanical, thermal, viscoelastic, and biodegradation properties 56,74,75,78,82,86,117,120,122,128–130,132,172,185 . Milovanovic et al 117 reported that the addition of 5 wt% PCL to PLA 2 film favored sorption of scCO 2 , decreased degradation temperature from 379.3 to 374.1°C, and T m from 161 to 154°C.…”
Section: Effect Of Process Variables On Pla‐based Materialsmentioning
confidence: 99%
“…In this context, material scientists look for solutions that keep the functionalities at use and have a minimum environmental impact [ 1 ]. Biocomposites properties have thus been investigated with a large variety of matrices and vegetal fiber reinforcements [ 2 , 3 ]. Poly lactic acid (PLA) notably is one of the main actors in biomaterials industrialization, targeting the packaging market.…”
Section: Introductionmentioning
confidence: 99%